PERCEPTION TOWARDS LECTURER’S CODE-SWITCHING IN EFL CLASSROOM OF STUDENTS AT THE AKADEMI KOMUNITAS MAPINDO FOOD AND BEVERAGE STUDY PROGRAM - Asriyani, Retny; Lindawati, Ni Putu (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2024)
Teaching English in Indonesia still faces several obstacles because not all students easily understand the meaning of what the Lecturer says in English. This greatly influences the students' success in understanding the material given, especially in completing the assignments or exams given. Therefore, most English language teaching and learning activities in Indonesia use code switching. Code switching is a change of language (switch) in communication, from one language to another Apart from that, code switching here means English to Indonesian or Indonesian to English. This research examines students of Akademi Komunitas MAPINDO food and beverages study program on the use of code switching in English Foreign Language (EFL) class. This research uses a qualitative research method with three instruments, namely questionnaire distribution, interviews and data collection. 28 students filled out the questionnaire, which is the total number from one class and these students are also involved in answering additional essay questions recognize the use of code switching in class. However, only 5 results were used to represent the entire class included in this research. The research results show that (1) the majority students agree to the use of code switching when it is taught in class (2) they perceive the existence of code switching help them improve their understanding of English language teaching (3) they think that Lecturers who use code switching are friendlier in teaching and better understand students' fluency in English (4) Students think that code switching can improve their readiness exam and pass (5) students feel confident when learning English by code switching and feel comfortable in class.